Basic Psychological Needs its impact on Sports Satisfaction, also the mediating role of dynamic relationship between Chinese Athletes and Coaches - Peng Xitao; Yang Shiqiang; Chenlin, Ying (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This study aims to create a measure for sport’s satisfaction and basic psychological needs in athlete and coach relation to providing evidence of initial reliability obtained from the measuring tool, Structural Equation Modelling. Basic Psychological Needs are affected by three dimensions: Competence, Relatedness, and Autonomy. For this study, a sample of 500 athletes and 500 coaches was collected from various athlete training centers in China. Autonomy, Relatedness, and Competence are considered natural psychological nutrients, and these nutrients play a significant role in the well-being, effective performance, and psychological development of athletes. The data was collected through self-administered and online questionnaires. The paper also discusses the Self-Determination Theory, as it supports the changes in the sport’s satisfaction level and basic psychological needs of coaches and athletes. In this research study, smart PLS software used different analysis such as descriptive statistic, tree analysis, test statistical, and the PLS Algorithm model. Result founded that there are positive and significant relation in between basic psychological need and sport satisfaction. Also that there are positive but insignificant relation in between coaches athletes and sport satisfaction